E-Community program: a study on ICT knowledge transfer to Labuan community - Wan Nooraishya Wan Ahmad; Ahmad Rizal Ahmad Rodzuan; Khan Vun Teong; Nuraini Jamil; Nooralisa Mohd Tuah (Springer, Cham, 2019)
The transfer of knowledge enables local communities to keep up with the current revolution of ICT and later to create a knowledge society. This study reviews knowledge transfer activities to local communities in Labuan through the E-Community Program conducted by the Faculty of Computing and Informatics (FCI), Universiti Malaysia Sabah Labuan International Campus (UMSLIC). The objective of this study is to investigate the trend of selecting and implementing e-community projects. The study was conducted quantitatively and qualitatively towards the e-community project reports as well as discussions between lecturers. The finding shows that graphic design projects are popular e-community projects and school students are the most benefited communities. Impacts, challenges and suggestions for improvements to the program are also discussed.